Censorship and the defense of intellectual freedom in the Lisbon Public Library Network - Andrade,Carolina João (2026)
This study investigates the emergence of user-driven censorship attempts within the Lisbon Public Library Network. The research is structured around three key dimensions: (1) the preparedness of library professionals to manage censorship attempts; (2) the challenges within these libraries; and (3) the professional culture concerning the defense of intellectual freedom. The findings suggest that although contestation remain infrequent, patterns are consistent with the challenges observed internationally, particularly those driven by politically motivated far-right groups. Additionally, the professional culture aligns with the principles of social librarianship, where librarians are viewed as agents of social change while maintaining a neutral stance.